2014
DOI: 10.1007/s13197-014-1518-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of technology for manufacture of ragi ice cream

Abstract: Ragi (Finger millet) improves the nutritional value of ice cream by enhancing the iron and fibre content. Caramel flavoured medium fat ice cream (6 % fat) was prepared by addition of gelatinized malted ragi flour roasted in butter (MRB) @ 8 %, 9 % and 10 % by weight of mix and compared with control (C) i.e. vanilla ice cream containing 10 % fat. The overall acceptability score of product prepared using 9 % MRB was statistically (P>0.05) at par with the C, hence, it was selected. In the next part of the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 38 publications
2
12
0
Order By: Relevance
“…These results were in agreement with those reported by. 23 They found that ice creams with the high level of gelatinized malted ragi flour had the highest melting resistance. They attributed that to fibers and starch in ragi flour which may act as stabilizers and thus caused increase in melting resistance of resultant ice cream.…”
Section: Physical Properties Of the Resultant Probiotic Frozen Yoghurtmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in agreement with those reported by. 23 They found that ice creams with the high level of gelatinized malted ragi flour had the highest melting resistance. They attributed that to fibers and starch in ragi flour which may act as stabilizers and thus caused increase in melting resistance of resultant ice cream.…”
Section: Physical Properties Of the Resultant Probiotic Frozen Yoghurtmentioning
confidence: 99%
“…Gelatinized starch has high water holding capacity and it can influence the rheological properties of frozen yoghurt mix. 22,23…”
Section: Sensory Evaluation Of Experimented Frozen Yoghurt Samplesmentioning
confidence: 99%
“…Cereals and milk are blended to compensate for deficiency of each other in a number of research studies (Aneja et al, 2002, Mugocha et al, 2000, Modha and Pal, 2011, Addis et al, 2013, Chaudhary, 2013, Pardhi et al, 2014, Shivakumar et al, 2014, Isingoma et al, 2015, Chilakawar et al, 2015, Patel et al,2015. While combining milk and cereal for obtaining nutritional benefits, it is essential that we need to understand the effect of level of cereal incorporation as well as the effect of its forms in the physico-chemical, sensory as well as microbiological aspects of the resultened product.…”
Section: Issn: 2319-7706 Volume 6 Number 9 (2017) Pp 2258-2266mentioning
confidence: 99%
“…Millets are classified with maize and sorghum in the grass sub-family Panicoideae [3,8]. They are the 6th most important cereal grain crop in the world agricultural production after wheat, maize, sorghum, rice, and barley that are regarded as the major economic grains in the world [13][14][15]. Millets are resistant to pests and diseases as compared to other cereal grains [1,13].…”
Section: Introductionmentioning
confidence: 99%